An economic efficiency study of Radio Frequency Identification (RFID) System in Bangko Sentral ng Pilipinas (BSP) Library using net present value analysis - Lagman, Jerome M. (2019)
Being the first and only implementation of Radio Frequency Identification system in the library, and economic efficiency study was performed in the Banko Sentral ng Pilipinas (BSP) library to determine if the implementation is economically efficient. The methodology used for the study is net present value analysis (NPV). Additional tools were used to support the NPV; these are cost-benefit ratio, and payback period. A sensitivity analysis was also used to reduce uncertainties in the study.